Factors influencing influenza vaccination coverage among kindergarten and primary school children in Zhejiang Province， 2023 - LI Minchao; TAO Jing; ZHANG Rui; WU Yumeng; HE Zhaokai; WU Chen (Shanghai yufang yixue)
ObjectiveTo investigate the influenza vaccination coverage among kindergarten and primary school children in Zhejiang Province in 2023 and analyze the influencing factors, and to provide the basis for improving the effect of influenza vaccination in children.MethodsA multi-stage random cluster sampling method was used to select 3 681 parents of children from 10 primary schools and kindergartens based on economic level and geographical distribution in Zhejiang Province, who participated in an online questionnaire survey, including basic information about the children and their parents, parents’ knowledge about influenza, and their willingness to vaccination.ResultsAmong the 3 681 parents surveyed, 33.82% (1 245/3 681) reported that their children received influenza vaccination in 2023. Multivariate logistic regression analysis showed that factors contributing to children’s influenza vaccination included both parents [adjusted OR (95%CI): 1.56 (1.32‒1.84)] and children [6.04 (5.04‒7.27)] having a history of influenza vaccination, parents’ conviction the influenza vaccine could protect children from severe diseases [1.43 (1.19‒1.74)], and the willingness of most parents would let their children get vaccinated [1.40 (1.13‒1.74)]. In contrast, vaccine hesitancy among parents [0.55 (0.43‒0.69)] and the belief that influenza is just a common cold [0.80 (0.65‒1.00)] were hindering factors.ConclusionThe influenza vaccination coverage among children is insufficient. Both the vaccination history of parents and children, as well as parents’ correct understanding of influenza and the effectiveness of influenza vaccine, significantly influence the influenza vaccination status in children. Efforts to address vaccine hesitancy and misconceptions about influenza are essential to improve vaccination rates.